The Influence of Corporate Governance on Financial Performance: The Case in The Indonesian Banking Sector - Esti Utami Pratiwi (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
This study examines the influence of corporate governance on financial performance. The management of the company should be supervised and controlled to ensure that management is carried out in full compliance with applicable rules and regulations. The existence of corporate governance as a mechanism of supervision and control is expected to improve the company's financial performance so as to increase the return on assets of the company. This study uses secondary data derived from the financial statements of banking companies listed on the Indonesia Stock Exchange in 2012-2016. This research uses the purposive sampling method and uses multiple linear regression analysis. Prior to the regression test, the data were first tested using the classical assumption test. The results of this study indicate that independent board of commissioners, board of commissioner size, managerial ownership, and audit committee have a negative effect on financial performance. The size of the board of directors has a positive and significant impact on financial performance. This proves that a large number of boards of commissioners and audit committees do not affect the financial performance of the company.